畢氏定理 證明 5

\begin{equation}作一線段\mathrm{AD}平分\angle\mathrm{CAB}並作線段\mathrm{DH},讓\mathrm{DH}\perp\mathrm{AB},\end{equation}

\begin{equation}則\triangle\mathrm{CAD}\cong\triangle\mathrm{HAD}\end{equation}

\begin{equation}\Rightarrow\angle\mathrm{BDH}=\angle\mathrm{CAB},\mathrm{CD}=\mathrm{DH}=\mathrm{x},\mathrm{AC}=\mathrm{AH}=\mathrm{b}\end{equation}

\begin{equation}\because\triangle\mathrm{ABC}\sim\triangle\mathrm{DBH}\end{equation}

\begin{equation}\therefore\mathrm{c}:(\mathrm{a}-\mathrm{x})=\mathrm{a}:(\mathrm{c}-\mathrm{b})\end{equation}

\begin{equation}\Rightarrow\mathrm{a}^2+\mathrm{bc}-\mathrm{ax}=\mathrm{c}^2\cdots\cdots(\mathrm{1})\end{equation}

\begin{equation}\therefore\mathrm{a}:(\mathrm{c}-\mathrm{b})=\mathrm{b}:\mathrm{x}\end{equation}

\begin{equation}\Rightarrow\mathrm{bc}-\mathrm{ax}=\mathrm{b}^2\cdots\cdots(\mathrm{2})\end{equation}

\begin{equation}將(\mathrm{2})代入(\mathrm{1})可以即可得到\end{equation}

\begin{equation}\Rightarrow\mathrm{a}^2+\mathrm{b}^2=\mathrm{c}^2\end{equation}

Reference:

1. Elisha S. Loomis (1935): « The Pythagorean Proposition ». p. 43.

發佈留言